Risk factor analysis of female soccer tournament players - Sasaki, S.; Kaneko, S.; Kobayashi, T. (Sports injuries and prevention, 2015)
In this study, a 2-dimensional (2-D) video analysis of anterior cruciate ligament injury events from the sagittal and coronal planes was introduced. Using a sagittal analysis, we analyzed the landing action after heading when no injury occurred and checked variables related to anterior cruciate ligament injury. We found that the trunk angle was similar when injury or no injury occurred, and the hip angle and the distance from the center of mass to the base of support (COM_BOS) were smaller in both injured and control participants compared to those reported in previous studies. Future video studies are planned to analyze not only injury but also non-injury events to develop a screening tool for risk factors.